Path analysis for grain yield in barnyard millet (Echinochloa frumentacea (Roxb.) link ) (Bangladesh Journal of Botany, 2015)
Path coefficient analysis was studied in 65 genotypes of barnyard millet to find out the association studies of characters and their direct and indirect effects on grain yield/plant. Results exhibited that single earhead weight had maximum direct effects on grain yield/plant followed by straw yield/plant, earhead length and plant height. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22739 Bangladesh J. Bot. 44(1): 147-150, 2015 (March)